2017
DOI: 10.1186/s12894-017-0204-8
|View full text |Cite
|
Sign up to set email alerts
|

The resonance® metallic ureteric stent in the treatment of chronic ureteric obstruction: a safety and efficacy analysis from a contemporary clinical series

Abstract: BackgroundWe evaluate the efficacy and safety of metallic ureteric stenting using the Cook Resonance® stent in the treatment of chronic ureteric obstruction of benign and malignant aetiology. Published experience of using this stent in this context is limited. We add to the body of literature on this topic.MethodsAll patients who had a Resonance® metallic stent inserted between April 2009 and November 2014 in our institution were identified from a prospectively maintained stent-database. Primary outcome was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Patel et al 5 reported 12 months median indwelling time of Resonance ® stent in the malignant ureteral obstruction group and 19 months in the non-malignant group of a 52 cases series. But most of the retrospective and prospective studies between the years of 2013 to 2016 report a median duration of 5-12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al 5 reported 12 months median indwelling time of Resonance ® stent in the malignant ureteral obstruction group and 19 months in the non-malignant group of a 52 cases series. But most of the retrospective and prospective studies between the years of 2013 to 2016 report a median duration of 5-12 months.…”
Section: Discussionmentioning
confidence: 99%
“…The patency rate of metallic stents for the treatment of MUO lies between 37% and 100% [1621], and the success rate of the operation is 96% [22], according to literature reports. In our study, the success rate of metallic stent catheterization was 96.9%.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 2 years we have replaced wallstents with thermoexpandable metallic stents (Memokath, PNM Medical, Denmark [8][9][10][11]). …”
Section: Methodsmentioning
confidence: 99%